1991
DOI: 10.1159/000110285
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Parkinson's Disease: A New Approach to Disability

Abstract: Testing the reliability and usefulness of disability scales in Parkinson''s disease has been the object of a study carried out by 4 neurologists on 48 patients using 2 rating scales – Hoehn and Yahr staging and Columbia University Rating Scale – and 2 disability scales – Northwestern University Disability Scale and Extensive Disability Scale, a new scale conceived for this purpose, which is more accurate in examining in a different way the physical incapacity and handicap of parkinsonian patients in their dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Although interobserver agreement has been assessed for several PD clinical rating scales (27)(28)(29)(30)(31) and even for the UPDRS, studies have not examined physician-patient agreement in the historical section of the UPDRS. Kivela (24) compared health care professionals' with patients' assessments of disability in 205 elderly persons with chronic disease and found 84-97% concordance for assessments of dressing, eating, washing, and bathing.…”
Section: Discussionmentioning
confidence: 99%
“…Although interobserver agreement has been assessed for several PD clinical rating scales (27)(28)(29)(30)(31) and even for the UPDRS, studies have not examined physician-patient agreement in the historical section of the UPDRS. Kivela (24) compared health care professionals' with patients' assessments of disability in 205 elderly persons with chronic disease and found 84-97% concordance for assessments of dressing, eating, washing, and bathing.…”
Section: Discussionmentioning
confidence: 99%
“…19 Others have reported interrater reliability, as measured by k w , at 0.77. 35 There are no reports of the test-retest reliability or internal consistency of the NUDS.…”
Section: The Timed Up-and-go Test (Tug)mentioning
confidence: 99%
“…From a factor analysis, assessed in one study, three factors were derived, including (I) arm swing, gait, self‐care and posture; (II) speech and facies; (III) seborrhea 19. Four studies showed that the scale displays poor to moderate inter‐rater reliability 23–28…”
Section: Clinimetric Characteristics Of the Included Scalesmentioning
confidence: 99%